Current understanding of allergic fungal rhinosinusitis. Issue 3 (1st September 2018) - Tyler, Matthew A.; Luong, Amber U.
Abstract : Studying the pathophysiology of allergic fungal rhinosinusitis (AFRS) has proved challenging. While this clinical entity is easily distinguishable based on the clinical criteria set forth by Bent and Kuhn twenty‐five years ago, studies examining type 2 inflammatory profiles in AFRS can make it seem more alike other CRS subtypes than it is different. Still, evolving research seems to clearly delineate this subtype from others in CRS. This review will critically evaluate the evolution of research examining the pathophysiology of AFRS and will conclude with a summary of the special considerations in the management of this fascinating disease.